Simulation of speech activities using Markov Model - Shah, Asadullah; Bhatti, Zeeshan (IIUM Press, 2011)
A speech signal can be active or non-active; in one of the nvo states in anyone time, or for a frame of speech. The duration ofthe both active and non-active parts can varies based upon the modes of speech (monologue and dialogue). The activities or non-activities of the speech can be modelled by using Markov Model, in this scenario a two state model, each activity is modelled by one of the states of the model. In this chapter a nvo state Markov model design is presented that model can be used for the simulation designs of STDM